Marketing Strategy Analysis in Increasing Sales Volume at Cafe Wong Paiton, Sapikerep Village, Probolinggo Regency - Kevin Ramadhany Sukmana; Yanda Bara Kusuma (Universitas KH. Abdul Chalim Mojokerto, 2025)
In the highly competitive cafe industry, effective marketing strategies are a key factor in achieving significant sales growth, the lack of understanding of these preferences is the background to the existence of research related to the analysis of marketing strategies in increasing sales at Cafe Wong Paiton Probolinggo, which is relevant and important to be carried out and uses the latest theories. The purpose of this study is to determine and analyze the marketing strategies used by Cafe Wong Paiton in increasing sales volume. This research is expected to be useful for the development of knowledge that has been learned by the researcher during his service in the Business Administration study program at the National Development University